Duality in Quantum Physics (British Journal of Multidisciplinary and Advanced Studies, 2025)
In this short paper we study duality as it appears in the quantum world after an extensive research on hidden variables. The landmark of this duality is Omega=-PV which is the last letter of the Greek alphabet, a thermodynamic quantity.